GAYA KEPEMIMPINAN TRANSFORMASIONAL UPAYA DAN SOLUSI - Astohar, Astohar (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2010)
Most of conflicts between subordinary and leader happened because of leadership style that not aceptable with subordinary. Subordinary often judge that their leader who manage the organization have an otoriter and straight behaviour, they never think about and subordinary needs.